Ganymede MHD Model: Magnetospheric Context for Juno's PJ34 Flyby. Issue 24 (20th December 2022) - Duling, Stefan; Saur, Joachim; Clark, George; Allegrini, Frederic; Greathouse, Thomas; Gladstone, Randy; Kurth, William; Connerney, John E. P.; Bagenal, Fran; Sulaiman, Ali H.
Abstract: On 7 June 2021 the Juno spacecraft visited Ganymede and provided the first in situ observations since Galileo's last flyby in 2000. The measurements obtained along a one‐dimensional trajectory can be brought into global context with the help of three‐dimensional magnetospheric models. Here we apply the magnetohydrodynamic model of Duling et al. (2014, https://doi.org/10.1002/2013ja019554 ) to conditions during the Juno flyby. In addition to the global distribution of plasma variables we provide mapping of Juno's position along magnetic field lines, Juno's distance from closed field lines and detailed information about the magnetic field's topology. We find that Juno did not enter the closed field line region and that the boundary between open and closed field lines on the surface matches the poleward edges of the observed auroral ovals. To estimate the sensitivity of the model results, we carry out a parameter study with different upstream plasma conditions and other model parameters. Plain Language Summary: In June 2021 the Juno spacecraft flew close to Ganymede, the largest moon of Jupiter, and explored its magnetic and plasma environment. Ganymede's own magnetic field forms a magnetosphere, which is embedded in Jupiter's large‐scale magnetosphere, and which is unique in the solar system. The vicinity of Ganymede is separated into regions that differ in whether the magnetic field lines connect to Ganymede's surface at both or one end or not at all. These regions are deformed by the plasma flow and determine the state of the plasma and the location of Ganymede's aurora. We perform simulations of the plasma flow and interaction to reveal the three‐dimensional structure of Ganymede's magnetosphere during the flyby of Juno. The model provides the three‐dimensional state of the plasma and magnetic field, predicted locations of the aurora and the geometrical magnetic context for Juno's trajectory. These results are helpful for the interpretation of the in situ and remote sensing obtained during the flyby. We find that Juno did not cross the region with field lines that connect to Ganymede's surface at both ends. Considering possible values for unknown model parameters, we also estimate the uncertainty of the model results. Key Points: Our magnetohydrodynamic model illustrates the state of Ganymede's magnetosphere during Juno's flyby and locates its trajectory outside closed field lines The location of the open‐closed‐field line‐boundary is predicted and matches the poleward edges of the aurora as observed by Juno We investigate model uncertainties caused by incomplete knowledge of upstream conditions and other parameters